2016
DOI: 10.4300/jgme-d-15-00321.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Generic Competencies in the Entrustment of Professional Activities: A Nationwide Competency-Based Curriculum Assessed

Abstract: Background Entrustable professional activities (EPAs) seek to translate essential physician competencies into clinical practice. Until now, it is not known whether EPA-based curricula offer enhanced assessment and feedback to trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…Anchor-based, milestone end-of-shift ratings are commonly used to inform summative evaluation by educators. However, recent literature suggests that the goal of "entrustment" in medical education is not reached by the attainment of generic anchors (van Loon, Teunissen, Driessen, & Scheele, 2016). In fact, an overestimation of resident proficiency and an inability to discriminate between residents of different levels of training have been described when utilizing milestone-based end-of-shift evaluations (Dehon, Jones, Puskarich, Sandifer, & Sikes, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Anchor-based, milestone end-of-shift ratings are commonly used to inform summative evaluation by educators. However, recent literature suggests that the goal of "entrustment" in medical education is not reached by the attainment of generic anchors (van Loon, Teunissen, Driessen, & Scheele, 2016). In fact, an overestimation of resident proficiency and an inability to discriminate between residents of different levels of training have been described when utilizing milestone-based end-of-shift evaluations (Dehon, Jones, Puskarich, Sandifer, & Sikes, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The same survey was performed three months after the implementation of the new system. To facilitate analysis, each level of agreement was assigned a numerical value (1)(2)(3)(4)(5). The results were aggregated, and were analyzed using t-tests, assuming unequal variances.…”
Section: Methodsmentioning
confidence: 99%
“…1 Previous research has shown that ad hoc entrustment decisions in the clinical setting are made by clinical supervisors primarily based on each resident's experience and exposure to a particular task, rather than generic cross-context competencies such as communication skills. 2 EPAs integrate competencies, which are not observable in isolation, into observable professional tasks, allowing direct assessment of the resident's work performance rather than attempting to infer competence based on underlying generic competencies.…”
Section: Introductionmentioning
confidence: 99%
“…We compared our label scheme with labels identified in earlier studies. 9,14 This led to a new structure, in which initial labels were combined into categories. Discussion with all authors (2 educational scientists and 2 faculty members) resulted in a final set of categories based on coded quotes.…”
Section: Bottom Linementioning
confidence: 99%